Burning the midnight oil: causes and consequences of gender differences in overtime in the federal service - Lewis, Gregory B. (1999)
The Merit Systems Protection Board's glass ceiling report worried that the inability of women with young children to work overtime may be unfairly hindering their career advancement. I investigated this possibility, using a large survey of federal employees. Overall, women were only 60% as likely as men to work overtime. Gender differences in both child care responsibilities and educational levels helped explain this pattern, as did differences in job demands. Among college-educated professionals and administrators, men's and women's overtime rates were quite similar, especially among employees at the same grade levels. Working overtime does appear to speed career advancement, especially for women, but overtime appeared to play a trivial role in gender inequality in pay, especially among the employees most likely to reach the top. - Reproduced
Keywords: Women in the civil service